Heterogeneity in Risk of Pelvic Inflammatory Diseases After Chlamydia Infection: A Population-Based Study in Manitoba, Canada - Davies,B; Ward,H; Leung,S; Turner,KME; Garnett,GP; Blanchard,JF; Yu,BN (Journal of Infectious Diseases, 2014)
Background. The association between chlamydia infection and pelvic inflammatory disease (PID) is a key parameterfor models evaluating the impact of chlamydia control programs. We quantified this association using aretrospective population-based cohort.Methods. We used administrative health data sets to construct a retrospective population-based cohort ofwomen and girls aged 12–24 years who were resident in Manitoba, Canada, between 1992 and 1996. We performedsurvival analysis on a subcohort of individuals who were tested for chlamydia to estimate the risk of PID diagnosed ina primary care, outpatient, or inpatient setting after ≥1 positive chlamydia test.Results. A total of 73 883 individuals contributed 625 621 person years of follow-up. Those with a diagnosis ofchlamydia had an increased risk of PID over their reproductive lifetime compared with those who tested negative(adjusted hazard ratio [AHR], 1.55; 95% confidence interval [CI], 1.43–1.70). This risk increased with each subsequentinfection: the AHR was 1.17 for first reinfection (95% CI, 1.06–1.30) and 1.35 for the second (95% CI,1.04–1.75). The increased risk of PID from reinfection was highest in younger individuals (AHR, 4.55 (95% CI,3.59–5.78) in individuals aged 12–15 years at the time of their second reinfection, compared with individualsolder than 30 years).Conclusions. There is heterogeneity in the risk of PID after a chlamydia infection. Describing the progression toPID in mathematical models as an average rate may be an oversimplification; more accurate estimates of the costeffectivenessof screening may be obtained by using an individual-based measure of risk. Health inequalities may bereduced by targeting health promotion interventions at sexually active girls younger than 16 years and those with ahistory of chlamydia.